Political selection in China: The complementary roles of connections and performance - Ruixue Jia; Masayuki Kudamatsu; David Seim (Research Institute of Industrial Economics (IFN), 2014)
Who becomes a top politician in China? We focus on provincial leaders - a pool of candidates for top political office - and examine how their chances of promotion depend on their performance in office and connections with top politicians. Our empirical analysis, based on the curriculum vitae of Chinese politicians, shows that connections and performance are complements in the Chinese political selection process. This complementarity is stronger the younger provincial leaders are relative to their connected top leaders. To provide one plausible interpretation of these empirical findings, we propose a simple theory in which the complementarity arises because connections foster loyalty of junior officials to senior ones, thereby allowing incumbent top politicians to select competent provincial leaders without risking being ousted. Auxiliary evidence suggests that the documented promotion pattern does not distort the allocation of talent. Our findings shed some light on why a political system known for patronage can still select competent leaders.
Keywords: H11; H70; J63; P30; 330; Political turnover; Economic performance; Personnel control; Social networks